GIS Application for Health Facility Coverage Mapping in Temanggung Regency, Central Java Province - Arga Geofana (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
Adequate health facilities have become one of the interesting issues to be discussed since this pandemic situation. Availability and accessibility of health facilities are the vital aspects that should be accomplished by both local and central government. Nevertheless, some population especially those living in rural areas have some difficulties in reaching these facilities due to the inequality condition within regions. This study aims to analyze the coverage of health facilities in Temanggung Regency, Central Java province and cluster its subdistricts according to their condition in accessing these facilities. The analysis is limited to public health facility (PUSKESMAS) and hospital levels. Both statistical and spatial data were processed using the GIS network analysis approach in producing the coverage number of each health facility and they were compared to the applied standard range of service and threshold. Then, a hierarchy is created using the weighted centrality index approach to represent disparities among subdistricts in Temanggung Regency regarding the availability and its coverage to health facilities. The results show that there is an inequality condition on health facilities coverage between central and peripheral areas within this regency, both at the public health facility level and hospital level. Several population in several districts, mostly residing in outer areas, are not covered by both public health facility and hospital. On the other hand, people in the capital and its surrounding subdistricts have better access to these facilities. Several factors are identified in producing this inequality, such as spatial distribution of housing areas, spatial allocation of health facilities, road network, and topographic condition. The topographic condition in some uncovered areas, which is relatively hilly and has steep slope, causes limited access to the road network and less coverage of health facilities.